A forgotten Pioneer: Guido Beck and the prediction of gravitational waves - S. da Cruz, Alexandre; Velloso, Rafael; Passos Videira , Antonio Augusto (Cadernos de Astronomia, 2025)
In 1925, the young Austrian physicist Guido Beck obtained the first exact solution to the equations of general relativity that exhibits the phenomenon of energy transport via gravitational waves. Despite its relevance and pioneering character, Beck’s work remained unknown to the physics community for decades. Here we present a translation into Portuguese of the original article, written in German, in which Beck presents these results, along with an overview of the early years of his career, when he worked in the field of general relativity.